Pengaruh Pembayaran Non-Tunai (E-Wallet) dan Gaya Hidup terhadap PerilakuKonsumtif Mahasiswa Universitas Nahdlatul Ulama Kalimantan Barat Angkatan 2020 - Saliyeh, Saliyeh; Firayanti, Yuni; Saputra, Edy Suchmawan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to determine the influence of non-cash payments (e-wallets) and lifestyle on the consumptive behavior of students at Nahdlatul Ulama University, West Kalimantan, class of 2020. This research uses quantitative methods and data collection techniques using questionnaires with a sample of 92 respondents. The data analysis technique used in this research is multiple linear regression analysis, namely the coefficient of determination test and hypothesis testing with the SPSS 23 program. The results of this research show that partially non-cash payments (e-wallets) have no effect on the consumptive behavior of students at Nahdlatul Ulama University, West Kalimantan, with a significance value of 0.496, which is greater than 0.05. On the other hand, lifestyle has a positive and significant effect on consumer behavior, with a significance value of 0.000, which is smaller than 0.05. The influence of non-cash payments (e-wallets) and lifestyle on the consumptive behavior of Nahdlatul Ulama University students in West Kalimantan is 36.8%, and the remaining 63.2% is influenced by other variables not examined in this research.